2016
DOI: 10.1111/1365-2656.12548
|View full text |Cite
|
Sign up to set email alerts
|

Experimental insight into the process of parasite community assembly

Abstract: Community assembly is a fundamental process that has long been a central focus in ecology. Extending community assembly theory to communities of co-infecting parasites, we used a gastrointestinal nematode removal experiment in free-ranging African buffalo to examine the community assembly patterns and processes. We first asked whether reassembled communities differ from undisturbed communities by comparing anthelmintic-treated and control hosts. Next, we examined the temporal dynamics of assembly using a cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 51 publications
(64 reference statements)
0
32
1
Order By: Relevance
“…Our work illustrates how between-host processes (prevalence and transmission) alter within-host dynamics via withinhost priority effects. To fully apply this framework to pathogen communities in other natural systems, we must understand how within-host priority effects function in species-rich pathogen and parasite assemblages (Budischak et al 2016). Further, we need to study whether within-host priority effects function in a discreet or continuous manner.…”
Section: Discussionmentioning
confidence: 99%
“…Our work illustrates how between-host processes (prevalence and transmission) alter within-host dynamics via withinhost priority effects. To fully apply this framework to pathogen communities in other natural systems, we must understand how within-host priority effects function in species-rich pathogen and parasite assemblages (Budischak et al 2016). Further, we need to study whether within-host priority effects function in a discreet or continuous manner.…”
Section: Discussionmentioning
confidence: 99%
“…spatial variation in exposure risk; Calabrese, Brunner, & Ostfeld, 2011) or interactions between dispersal and drift (e.g. priority effects; Budischak et al, 2016). Overall, parasite interactions and variation in host competency or exposure risk did not appear to be important processes in this system.…”
Section: Discussionmentioning
confidence: 99%
“…For example, by partitioning variance in community composition across scale and over time, Costello et al (2009) showed that temporal variation in gut microbiomes within the same individual was smaller than among‐individual variation, even on the same day, suggesting that different hosts selected particular microbial communities that remained distinct from other hosts’ microbiota over time. Temporal analyses of parasite community composition are still relatively rare (but see Budischak, Hoberg, Abrams, Jolles, & Ezenwa, 2016; Cohen et al, 2015; Fallon, Ricklefs, Latta, & Bermingham, 2004; Vidal‐Martínez & Poulin, 2003), and even fewer studies have longitudinally tracked parasite community composition across multiple distinct scales to infer the general processes driving assembly.…”
Section: Introductionmentioning
confidence: 99%
“…While the tick-borne parasites (e.g., TP, Anaplasma spp.) (22), Coccidia, nematodes, and flukes (21,46,47) were diagnosed by the presence of the parasite itself, the remaining parasites were considered present when a buffalo's antibody status went from negative to positive between 2 captures (48). Because buffalo are not known to clear Br (49) or BVDV (50,51), once an animal seroconverted, it was considered positive for the remainder of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Investigators have begun to apply community ecological principles to the field of disease ecology to understand parasite interactions within a host (4,(11)(12)(13)(14)(15), although most studies still break existing networks of parasites into isolated pairwise comparisons (e.g., refs. [16][17][18][19][20][21][22] that may fail to capture the true dynamics of coinfection.…”
mentioning
confidence: 99%